2004
DOI: 10.1254/jphs.fpj04004x
|View full text |Cite
|
Sign up to set email alerts
|

Acidic Oligosaccharide Sugar Chain, a Marine-Derived Acidic Oligosaccharide, Inhibits the Cytotoxicity and Aggregation of Amyloid Beta Protein

Abstract: Abstract. In this paper, we investigated interactions of the acidic oligosaccharide sugar chain (AOSC), derived from brown algae Echlonia kurome OKAM, with amyloid beta protein (Ab). We observed that AOSC inhibited the toxicity induced by Ab in both primarily cortical cells and the SH-SY5Y cell line. We also observed that AOSC inhibited the apoptosis induced by Ab in SH-SY5Y by reducing the elevated level of intracellular calcium concentration ([Ca 2+ ] i ) and suppressing the generation of reactive oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 29 publications
0
45
0
Order By: Relevance
“…Although the effect of osmolytes or sugars have been experimentally investigated discretely, 13,31,32 absence of experimental data using a series of osmolytes prompted our study. Lerbret et al 48 reported stabilization of lysozyme in presence of disaccharides using molecular dynamics simulation and stated that ''the addition of sugars significantly reduces lysozyme fluctuations…..''.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effect of osmolytes or sugars have been experimentally investigated discretely, 13,31,32 absence of experimental data using a series of osmolytes prompted our study. Lerbret et al 48 reported stabilization of lysozyme in presence of disaccharides using molecular dynamics simulation and stated that ''the addition of sugars significantly reduces lysozyme fluctuations…..''.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PFF-A inhibited amyloid precursor protein biosynthesis and showed very strong BACE1 inhibitory activity, with a submicromolar IC 50 , making it an interesting potential drug candidate for AD ). An oligosaccharide sugar chain derived from EK inhibited the toxicity induced by the Ab protein in both primary cortical cells and the SH-SY5Y cell line, inhibiting apoptosis and fibril formation and indicating its potency for AD (Hu et al 2004). EM exhibited potent activity against AChE, as did its isolated compounds PG, dibenzo [1,4] dioxine-2,4,7,9-tetraol, and eckol, highlighting its potential as a functional food ingredient for the management of neurodegenerative disorders (Kannan et al 2013).…”
Section: Neuroprotective Activitymentioning
confidence: 97%
“…11 Similarly, an acidic oligosaccharide sugar chain (AOSC) inhibited the formation of β-amyloid induced fibrils and increased cell viability in primary cortical neurons. 12 Sterols [(23E)-3β-hydroxystigmasta-5,23-dien-28-one and (22E)-3β-hydroxycholesta-5,22-dien-24-one], bisindole alkaloids (Racemosa A and Racemosa B) and terpenoids (α-tocospirone) increased the viability of SH-SY5Y cells. 13 …”
Section: A R T I C L E I N F O Abstractmentioning
confidence: 99%